THE PREPOSITION NGANTI IN JAVANESE LANGUAGE - Ari Wulandari (Journal of English Language Teaching and English Linguistics, 2015)
This essay is under auspice of structural linguistics, which is mean to describe the prepositionnganti in Javanese language, understanding, how to use, what kind of categorial coconstituent whichis determined the presence, what is function, and what semantic role of prepositional phrases.Therefore, this essay uses descriptive qualitative method and a contact approach. This essay shows theresult the presence of the preposition nganti in the sentence is not determined by the filler predicatescategory, but is determined by the coconstituent category which can be seen from the use. Categoricaltypes of constituents that determine the presence of the preposition nganti are five categories, namelynouns (concrete, abstract), adjectives, numerals, adverbs (temporal, qualitative, size), and verbs(active, adversative). The preposition nganti function is as a boundary ending marker (time, place,number, size), a purpose marker, and an effect marker.